DINAMIKA BELIS DALAM ADAT PERKAWINAN MASYARAKAT ROTE BA`A DI KELURAHAN MOKDALE KECAMATAN LOBALAIN KABUPATEN ROTE NDAO - Tenabolo Dade, Yacobus (Humanis; Volume 1. No. 1. November 2012, 2016)
Marriage is a transitional period in human life. To carry out the marriage takes some conditions such as dowry (bride price), the outpouring of energy to mating (bride service) and sharing the girl (bride exchange). Dowry in the language of the community Rote Ba `a called belis consisting of animal buffalo (kamba ina), pigs (bafi), goats (bibi heik) and sheep (bibi lombo), has a shortage and the price is very high, thus making people think how to be a more practical way to match belis payment capabilities. Though dowry is an absolute requirement that has a function as an instrument of ratification of marriage, the economic, social and moral.Belis also significant as a symbol of kinship and reciprocity relations activator. Changes that occur only in the form of belis, in antiquity using animals, but now it can be replaced with a cash value.